Internal Causes of the Fall of the Emirates in The Islamic Mashreq During The 3rd And 4th A.H / 9th And 10th A.D Centuries - Mohammed, Shamal H.; Tawfiq, Zarrar S. (Humanities Journal of University of Zakho, 2019)
The emergence of the Islamic Emirates in the Mashreq during the Abbasid period in the 3rd and 4th A.H / 9th and 10th A.D centuries, was one of the most important events in Islamic history in general and the Abbasid Caliphate in particular. Several local factors contributed to the weakness and demise of the Islamic Emirates in the Mashreq. I addressed the inhert power, after that the weakness of the sultans who They took power, also administration weakness, In addition, economical reason, as well as internal conflicts over power, finally (Ibn Khaldun's)(D 808 A.H / 1405 A.D) theory regarding the age of the state and its application to those emirates and countries.